An Analysis of Behaviour Change Techniques Used in a Sample of Gestational Weight Management Trials - H. Soltani; M. A. Arden; A. M. S. Duxbury; F. J. Fair (Hindawi Limited, 2016)
Introduction. Maternal obesity and excessive gestational weight gain are associated with multiple adverse outcomes. There is a lack of clarity on the specific components of effective interventions to support pregnant women with gestational weight management. Method. All 44 studies within a preexisting review of lifestyle interventions, with a potential to impact on maternal weight outcomes, were considered for content analysis. Interventions were classified using Behaviour Change Technique (BCT) taxonomy clusters to explore which categories of BCT were used in interventions and their effectiveness in managing gestational weight gain. Results. The most commonly used BCTs were within the categories of "feedback and monitoring," "shaping knowledge," "goals and planning," "repetition and substitution," "antecedents," and "comparison of behaviours." For diet and mixed interventions "feedback and monitoring," "shaping knowledge," and "goals and planning" appeared the most successful BCT categories. Conclusions. Poor reporting within studies in defining the BCTs used, in clarifying the differences in processes between intervention and control groups, and in differentiating between the intervention and research processes made BCT classification difficult. Future studies should elaborate more clearly on the behaviour change techniques used and report them accurately to allow a better understanding of the effective ingredients for lifestyle interventions during pregnancy.